EFFECT OF CENTELLA ASIATICA POWDER (CAP) AND MANGOSTEEN PEEL POWDER (MPP) ON RUMEN FERMENTATION AND MICROBIAL POPULATION IN SWAMP BUFFALOES - T. Norrapoke; M. Wanapat; S. Wanapat; S. Foiklang (Journal of Animal and Plant Sciences, 2014)
Four, rumen-fistulated swamp buffalo bulls were randomly assigned to receive dietary treatments according to a 4x4 Latin square design. Four treatments were as follows; un-supplementation (control); supplementation with Centella asiatica powder (CAP) at 25 g/kg; supplementation with Mangosteen peel power (MPP) at 25 g/kg; CAP at 25 g/kg and MPP at 25 g/kg (CAMP) of total dry matter intake (DMI). Animals were fed with concentrate at 30 g/kg BW. Rice straw, water and mineral salt block were offered ad libitum. The experiment was conducted for 4 periods, and each period lasted for 21 days, while the last 7 days was for sample collection. The results revealed that the proportion of ruminal acetic acid was decreased whereas propionic acid increased (P<0.05) by supplementation as compared to control group. Similarly, methane emission was lesser (P<0.05) in the CAP and CAMP as compared to control group. While, ruminal protozoal population was dramatically decreased (P<0.05) with the CAP and MPP supplementation; whilst, the CAMP treatment had a higher (P<0.05) fungal zoospore population when compared to the control group. Moreover, community of DNA was extracted from 0.5 g of rumen fluid and digesta by the repeated bead beating plus column (RBB+C) method, Real-time PCR amplification and detection were performed in a Chromo 4™ system (Bio-Rad, USA), the use of real-time PCR technique provided the data that the population of protozoa was reduced (p<0.05) by CAMP supplementation; whereas instead, the population of F. succinogenes were increased (p<0.05) by the CAP and CAMP supplementation. Dietary supplementation had no effect on total bacterial population, and R. flavefaciens, R. albus.  In conclusion, CAP or MPP supplementation improved rumen fermentation by positively affecting the ruminal microbial population in swamp buffaloes fed on rice straw.
Keywords: Centella asiatica powder; mangosteen peel powder; rumen fermentation; methane production; real-time PCR; swamp buffaloes; rice straw